Solute carriers as potential oncodrivers or suppressors: their key functions in malignant tumor formation. Issue 7 (July 2021) - Rashid, Khalid; Ahmad, Aqeel; Liang, Li; Liu, Mengling; Cui, Yuehong; Liu, Tianshu
Graphical abstract: Highlights: SLCs play a key part in the metabolically driven tumor growth and metastasis. SLCs can exert both tumor-promoting as well as suppressive functions in cancers. In contrast to ABC transporters, SLCs can carry both influx and efflux process. SLCs can activate various signaling cascades that support tumor promoting functions. SLCs could serve as potential therapeutic targets for effective cancer treatment. Abstract : Solute carrier (SLC) transporters are primarily known for their function in the transportation of various exogenous/endogenous substances via influx/efflux mechanisms. In addition to their diverse role in several tumor-modulating functions, such as proliferation, migration, angiogenesis, epithelial–mesenchymal transition (EMT), epigenetic modification, chemoresistance, immunoregulation, and oncometabolism, influx/efflux-independent contributions of SLCs in the activation of various signaling network cascades that might drive metastatic tumor formation have also been uncovered. Disappointingly, even after two decades and the discovery of >450 SLCs, many of their members remain orphans in terms of cancer pathogenesis. In this review, we summarize the current understanding of the tumor-modulating functions, mechanisms, and complexity of SLCs, as well as their potential as targets for cancer therapy.